Entre o oralismo e a surdidade: mães ouvintes e a educação de crianças surdas - Melgueiro, Danielle dos Santos de Andrade (2024)
This research aims to understand the process that hearing mothers of deaf children are subjected to when choosing the type of education for their daughters and sons, which ranges from the diagnosis of deafness to the choice of the educational institution, and, therefore, the pedagogical methodology that will be applied to the child. As a general objective of analyzing oralism as a discursive practice and its impacts on deaf subjects in the acquisition of their mother tongue (LIBRAS) and in the production of deaf culture, we use Michel Foucault's (1979; 1997) power analysis to understand the network of power relations in production of knowledge that elected oralism as a hegemonic device in the education of the deaf since the Milan Congress of 1880 and we use Paddy Ladd's (2013) concept of Deafness to name the process of resistance of deaf culture in its various modalities as resistance to the imposition of oralism, and We call this game of power between Oralism and Deafness the Deafness Device. This work uses a qualitative methodology, through interviews with students from the Libras language course at UFAM, the results found were that hearing mothers of deaf children, due to their complete ignorance of deaf culture, opt, at least initially, for the conception of deafness as a disability to be remedied, this due to medical guidelines predominantly focused on oralism, and that in the course of children's growth and the emergence of psychosocial problems realize the need to know the deaf culture to provide better education and upbringing for their daughters and sons, which leads to the search for knowledge and training in the area.